PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI SEKRETARIAT DPRD PROVINSI JAWA TENGAH - Kharina Andita Mulyawarman; Susi Sulandari; Dyah Hariani (Journal of Public Policy and Management Review, 2021)
Various kinds of problems faced by the DPRD Secretariat of Central Java Province, including the lack of quality/competence and quantity of DPRD Secretariat apparatus resources in balancing advances in information technology and early detection of changes to laws and regulations. This study was prepared with the aim of describing work ability, work motivation, and work performance of the employees of the DPRD Secretariat of Central Java Province; determine the magnitude of the influence of work ability on the work performance of the Secretariat of the DPRD of Central Java Province; determine the magnitude of the influence of work motivation on the work performance of the Secretariat of the DPRD of Central Java Province; find out together the magnitude of the influence of work ability and work motivation on the work performance of the employees of the DPRD Secretariat of Central Java Province. The theory used in this research is Gibson's theory for work ability, Wijono's theory for work motivation, Sutrisno's theory for work performance. The method used in this research is explanative quantitative. The data analysis method used is quantitative analysis, namely Reliability Test and Validity Test, Kendall Tau Correlation Coefficient, Kendall W Concordance Coefficient, Coefficient of Determination. The results showed that the overall work ability variable (X1) was good with an average of 2.76, the work motivation variable (X2) was overall good with an average of 2.76, the work performance variable (Y) was overall good with an average of 2. an average of 2.66, work ability affects work performance by 73.3%, work motivation affects work performance by 73%, work ability and work motivation simultaneously affect work performance by 76.8%. The independent variable that most dominantly affects the work performance of the DPRD Secretariat of Central Java Province is the work ability variable. Further research is recommended to use other independent variables, namely environmental variables.